Răspuns :
x = 5 si a + b = 13
a) 3 × X + 7 × a + 7 × b = 3 × 5 + 7 × ( a + b ) = 15 + 7 × 13 = 15 + 91 = 106
______________________________________________________
b) 10 × X + ( 4 × a + 4 × b ) = 10 × 5 + 4 × ( a + b ) = 50 + 4 × 13 = 50 + 52 = 102
_________________________________________________________
c) X × a + X × b - 50 = X × ( a + b ) - 50 = 5 × 13 - 50 = 65 - 50 = 15
___________________________________________________
d ) ( 4 × a + 4 × b - 2 × X ) × ( 2 × a + 2 × b + X ) = 1 302
= [ 4 × ( a + b ) - 2 × 5 ] × [ 2 × ( a + b ) + 5 ] =
= ( 4 × 13 - 10 ) × ( 2 × 13 + 5 ) =
= ( 52 - 10 ) × ( 26 + 5 ) =
= 42 × 31 =
= 1 302
__________________________________________
2 )
a) ab + ac = a × ( b + c ) = 2 × 50 = 100
b) ab - ac = a × ( b - c ) = 7 × 100 = 700